Microstructure and mechanical behavior of laser aided additive manufactured low carbon interstitial Fe49.5Mn30Co10Cr10C0.5 multicomponent alloy. (30th June 2021) - Chew, Y.; Zhu, Z.G.; Weng, F.; Gao, S.B.; Ng, F.L.; Lee, B.Y; Bi, G.J.
Abstract: Laser aided additive manufacturing (LAAM) was used to fabricate bulk Fe49.5 Mn30 Co10 Cr10 C0.5 interstitial multicomponent alloy using pre-alloyed powder. The room temperature yield strength ( σ y ), ultimate tensile strength ( σ UTS ) and elongation ( ε UTS ) were 645 MPa, 917 MPa and 27.0 % respectively. The as-built sample consisted of equiaxed and dendritic cellular structures formed by elemental segregation. These cellular structures together with oxide particle inclusions were deemed to strengthen the material. The other contributing components include dislocation strengthening, friction stress and grain boundary strengthening. The high εUTS was attributed to dislocation motion and activation of both twinning and transformation-induced plasticity (TWIP and TRIP). Tensile tests performed at −40 °C and −130 °C demonstrated superior tensile strength of 1041 MPa and 1267 MPa respectively. However, almost no twinning was observed in the fractured sample tested at −40 °C and −130 °C. Instead, higher fraction of strain-induced hexagonal close-packed (HCP) ε phase transformation of 21.2 % were observed for fractured sample tested at −40 °C, compared with 6.3 % in fractured room temperature sample.